A multinomial logistic regression model-based seismic risk assessment method for museum exhibition halls. (15th June 2023) - Yang, Weiguo; Zou, Xiaoguang; Wang, Meng; Liu, Pei
Abstract: Earthquakes may damage not only museum buildings but also museum artifacts, which has raised concerns worldwide. Although there has been a growing interest in the protection of cultural heritage structures and individual art objects from seismic excitations, there remains a lack of a scientific methodology for the seismic risk assessment of museum exhibition halls where many artifacts are on display. In this work, a seismic risk assessment method for museum exhibition halls is proposed, and the Yuan Dynasty porcelain exhibition hall of the Capital Museum located in Beijing, China, is selected as a representative case for demonstration. Via the proposed method, the seismic fragility analysis of museum exhibition halls is performed on the basis of a developed multinomial logistic regression model. The risk values are then determined from the results of the site hazard and seismic fragility analysis. Finally, a simple fuzzy model is applied to realize the seismic risk assessment according to the calculated risk values. The method considers the detailed geometry of the artifacts, their support conditions, the dynamic response of the showcase, and the floor acceleration amplification of the museum structure. The proposed method can serve as a scientific analytical means by which to assess the seismic risk of museum exhibition halls for the preservation of cultural artifacts. Highlights: A seismic risk assessment method for museum exhibition halls is proposed. A multinomial logistic regression model was applied to achieve the seismic fragility analysis of exhibition halls. Seismic risk assessment of Yuan Dynasty porcelain exhibition hall of the Capital Museum was performed. Factors affecting the seismic safety of museum artifacts were discussed based on numerical study results.